THE EFFECTIVENESS OF GROUP-BASED PSYCHOEDUCATION IN REDUCING STRESS LEVELS IN PEOPLE WITH DIABETES MELLITUS TYPE 2 : A SYSTEMATIC REVIEW - Agus Sriyono; Eko Winarto; Witri Hastuti; Sabina Gero (Nursing Sciences Journal, 2026)
Type 2 Diabetes Mellitus is often accompanied by diabetes distress, which can impair self-management and glycemic control. Group-based psychoeducation has been developed as a psychosocial intervention to address this issue. Objective: This study aims to analyze the effectiveness of group-based psychoeducation in reducing stress in patients with type 2 diabetes mellitus through a systematic review approach. This study used a systematic review design following of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The PICO framework includes Population = type 2 diabetes mellitus patients; Intervention = group-based psychoeducation; Comparison = standard care or control conditions; Outcome = diabetes distress. Articles were systematically searched from PubMed, Scopus, Google Scholar, and ScienceDirect. Thirteen studies from various countries, predominantly randomized controlled trials and quasi-experiments, were included. The findings consistently showed that group-based psychoeducation significantly reduced diabetes distress compared to standard care or baseline conditions. Additional benefits included improved self-efficacy, better self-care behaviors, and improved glycemic control (HbA1c). Group-based psychoeducation is effective in reducing diabetes distress and supporting self-management in patients with Type 2 diabetes mellitus. It is recommended to integrate this intervention into routine nursing care through structured group programs and continuous evaluation to optimize patient outcomes.